Regioselective Synthesis of 2-Acylbutadienes from β,γ-Unsaturated Ketones - Shabalin, Dmitrii A.; Ivanova, Elena V.; Ushakov, Igor A.; Schmidt, Elena Yu.; Trofimov, Boris A. (Synthesis, 2019)
2-Acylbuta-1,3-dienes have been synthesized regioselectively from aromatic and heteroaromatic β,γ-unsaturated ketones (readily accessible via base-catalyzed addition of ketones to acetylenes) and aldehydes. The reaction smoothly proceeds with piperidine (10 mol%)/acetic acid (10 mol%) catalytic pair in boiling toluene to provide synthetically attractive polyconjugated electron-deficient dienes in up to 94% yield.
Keywords: condensation; C–C bond formation; unsaturated ketones; aldehydes; conjugated dienes